Design optimization of a new homogeneous reactor for medical radioisotope Mo-99/Tc-99m production. (July 2015) - Liem, Peng Hong; Tran, Hoai Nam; Sembiring, Tagor Malem
Abstract: To partly solve the global and regional shortages of Mo-99/Tc-99m supply, a conceptual design of a homogeneous solution reactor for Mo-99/Tc-99m medical radioisotope production is proposed. Some basic characteristics and features of the design are discussed. The new homogeneous solution reactor is designed by taking into account the matured technology for chemically extracting the Mo-99 from the low enriched uranium (LEU) targets (the modified LEU Cintichem process) that has been acquired, demonstrated and licensed commercially for decades by the Center for Radioisotope Production of the National Nuclear Energy Agency of Indonesia (BATAN). Design optimization for obtaining the minimum critical U-235 mass and the maximum reactor power (proportional to Mo-99 production capacity) is presented. Highlights: A new homogeneous reactor design for Mo-99/Tc-99m radioisotope production is proposed. The design takes into account the modified LEU Cintichem process for Mo-99 extraction. The design optimization is conducted to obtain minimum critical U-235 mass required.